Addressing Racism's Role in the US HIV Epidemic: Qualitative Findings From Three Ending the HIV Epidemic Prevention Projects. (1st July 2022) - Harrison, Sayward E.; Muessig, Kathryn; Poteat, Tonia; Koester, Kimberly; Vecchio, Alyssa; Paton, Mariajosé; Miller, Sarah J.; Pereira, Nastacia; Harris, Orlando; Myers, Janet; Campbell, Chadwick; Hightow-Weidman, Lisa
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Racist socio-political and economic systems in the United States are root causes of HIV disparities among minoritized individuals. However, within HIV implementation science literature, there is scarce empirical research on how to effectively counter racism. This article names racism and White supremacy as key challenges to the success of the Ending the HIV Epidemic (EHE) initiative and delineates opportunities to integrate anti-racism into HIV interventions. Methods: Formative data were synthesized from 3 EHE studies in California, North Carolina, and South Carolina. Each study engaged with community stakeholders to inform pre-exposure prophylaxis interventions. Key informant interviews and focus groups were used to query individuals—including Black individuals—about implementation challenges. Although racism was not an a priori focus of included studies, discourse on race and racism emerged as key study findings from all projects. Results: Across diverse stakeholder groups and EHE locales, participants described racism as a threat to the success of the EHE initiative. Institutional and structural racism, intersectional stigma, and maltreatment of minoritized individuals within healthcare systems were cited as challenges to pre-exposure prophylaxis scale-up. Some recommendations for addressing racism were given—yet these primarily focused on the individual level (eg, enhanced training, outreach). Conclusions: EHE implementation scientists should commit to measurable anti-racist actions. To this end, we present a series of recommendations to help investigators evaluate the extent to which they are taking actionable steps to counter racism to improve the adoption, implementation, and real-world impact of EHE interventions for people of color.